2022
DOI: 10.1101/2022.04.19.488835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Slowing of Frontocentral Beta Oscillations in Atypical Parkinsonism

Abstract: Diagnosis of atypical parkinsonian syndromes mostly relies on clinical presentation as well as structural and molecular brain imaging. It has not been investigated whether cortical oscillatory activity exhibits features distinguishing these syndromes. Therefore, we measured resting-state magnetoencephalography in 13 patients with corticobasal syndrome, 10 patients with progressive supranuclear palsy, 23 patients with idiopathic Parkinson’s disease and 23 healthy controls. We compared spectral power as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 97 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…After decades of literature suggesting a pathological shift in neurophysiological signal power from high to low frequencies in patients with neurodegenerative disorders 10-12,39-41,75-84 , recent advances in capturing these multi-spectral effects have documented their anatomical distribution and relevance to clinical features 19,42,52 . In the current work, we advance this line of research in patients with Parkinson’s disease using a marker of neurophysiological slowing that recently showed associations with cognitive impairments and amyloid proteinopathy in patients with Alzheimer’s disease 52 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After decades of literature suggesting a pathological shift in neurophysiological signal power from high to low frequencies in patients with neurodegenerative disorders 10-12,39-41,75-84 , recent advances in capturing these multi-spectral effects have documented their anatomical distribution and relevance to clinical features 19,42,52 . In the current work, we advance this line of research in patients with Parkinson’s disease using a marker of neurophysiological slowing that recently showed associations with cognitive impairments and amyloid proteinopathy in patients with Alzheimer’s disease 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, beta-band (15 – 30 Hz) activity is hypersynchronous across the cortico-basal ganglia circuit in patients with PD 17,29-33 , relates to severity of motor dysfunction, and can be normalized by common therapeutics 34-38 . In the cortex of patients with PD, decades of electrophysiological studies have demonstrated a stereotyped pattern of frequency-defined neural changes relative to healthy adults, including both increased activity in low-frequency bands (e.g., delta [2 – 4 Hz] and theta [5 – 7 Hz]) and concurrent decreased power in high-frequency bands (e.g., alpha [8 – 12 Hz] and beta) 12,39-42 . This has led to a hypothesized slowing of brain activity in patients with PD, but it remains unclear whether such a neurophysiological effect relates to clinical features of the disease, and whether any such relationships are of a deleterious or compensatory nature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also emphasize that few studies so far 10, 2931, 67, 68 have considered the respective associations of rhythmic and arrhythmic neurophysiological activity with PD. Yet, pathological changes in rhythmic versus arrhythmic electrophysiology call for distinct mechanistic interpretations.…”
Section: Discussionmentioning
confidence: 91%
“…To make spectra comparable between patients, the aperiodic component was modeled using the fitting oscillations and one over f algorithm and then subtracted from the power spectrum 31 . The aperiodic and periodic components were visually inspected, and the model order was adapted, if necessary, to ensure a good model fit 32 …”
Section: Discussionmentioning
confidence: 99%